How Teachers’ Roles Shape Adult Literacy Learners’ Engagement in Instruction - Hal Beder (Adult Education Research Conference, 2006)
This paper addresses the question: What are the contextual factors that shape learners’ engagement in adult literacy education? Six adult literacy classes were studied at an urban adult learning center. Data sources included video, traditional ethnographic observation, stimulated recall interviews and open interviews. Findings focus on the ways that teachers’ roles shape engagement.
Keywords: Adult literacy; engagemen